Natural inhibitors: A sustainable way to combat aflatoxins - Ahmad, Malik M.; Qamar, Firdaus; Saifi, Monica; Abdin, Malik Zainul (Frontiers in Microbiology, 2022)
Among few hundred mycotoxins, aflatoxins had always posed a major serious threat worldwide. Apart from Aspergillus species, aflatoxins are also synthesized by a number of fungal bodies including Fusarium, Penicillium, and Alternaria however A. flavus, A. parasiticus and A. nomius are the most toxin producing strains. Mainly, four different types of aflatoxins are produced as their secondary metabolites-Aflatoxin B1 (AFB1), Aflatoxin B2 (AFB2), Aflatoxin G1 (AFG1), Aflatoxin G2 (AFG2). There are certain other types of aflatoxins are found but they are the by-products of these toxins. The fungal agents generally infect the food crops during harvesting, storing and/or transporting; making a heavy post-harvest and economic loss in both developed as well as in developing countries. And while ingesting the crop products, these toxins make get into the dietary system causing aflatoxicosis, liver cirrhosis, etc. Therefore, it is imperative to search for certain ways to control the spread of infections and/or production of these toxins which may also not harm the crop harvest. In this review, we are going to discuss some sustainable methods that can effectively control the spread of infection and inhibit the biosynthesis of aflatoxins.